2014
DOI: 10.1136/jnnp-2014-308722
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations of scrub typhus

Abstract: Meningoencephalitis/encephalopathy may be seen in two-third of patients with scrub typhus. Scrub typhus should be included in the differential diagnosis of febrile encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 27 publications
8
106
0
Order By: Relevance
“…Eschar is found in 7-80% patients of scrub typhus [3]. In the authors study, eschar was detected in 28.81% of the patients of scrub typhus and 30.77% patients of meningoencephalitis due to scrub typhus [6]. The wide range of detection may be due to the difficulty in detecting eschars in dark-skinned individuals, difference in the eschar inducing capacity of the different strains of O. tsutsugamushi.…”
Section: Clinical Featuresmentioning
confidence: 86%
See 4 more Smart Citations
“…Eschar is found in 7-80% patients of scrub typhus [3]. In the authors study, eschar was detected in 28.81% of the patients of scrub typhus and 30.77% patients of meningoencephalitis due to scrub typhus [6]. The wide range of detection may be due to the difficulty in detecting eschars in dark-skinned individuals, difference in the eschar inducing capacity of the different strains of O. tsutsugamushi.…”
Section: Clinical Featuresmentioning
confidence: 86%
“…By this, it was suggested that the Karp and Boryong genotypes possibly invade the CNS more than other types [4]. In the author's study, tuberculous meningitis remained the close differential diagnosis of scrub typhus meningitis due to similar CSF findings [6]. However, CSF adenosine deaminase (ADA) may be helpful, as it is elevated >10 in tuberculous meningitis, unlike scrub typhus meningitis.…”
Section: Diagnosis Of Scrub Typhusmentioning
confidence: 89%
See 3 more Smart Citations